Synapses and dendritic spines are eliminated in the primary visual cortex of mice subjected to chronic intraocular pressure elevation - Xinyi Zhang; Deling Li; Weiting Zeng; Yiru Huang; Zongyi Zhan; Yuning Zhang; Qinyuan Hu; Lianyan Huang; Minbin Yu (Neural Regeneration Research, 2026)
Synaptic plasticity is essential for maintaining neuronal function in the central nervous system and serves as a critical indicator of the effects of neurodegenerative disease. Glaucoma directly impairs retinal ganglion cells and their axons, leading to axonal transport dysfuntion, subsequently causing secondary damage to anterior or posterior ends of the visual system. Accordingly, recent evidence indicates that glaucoma is a degenerative disease of the central nervous system that causes damage throughout the visual pathway. However, the effects of glaucoma on synaptic plasticity in the primary visual cortex remain unclear. In this study, we established a mouse model of unilateral chronic ocular hypertension by injecting magnetic microbeads into the anterior chamber of one eye. We found that, after 4 weeks of chronic ocular hypertension, the neuronal somas were smaller in the superior colliculus and lateral geniculate body regions of the brain contralateral to the affected eye. This was accompanied by glial cell activation and increased expression of inflammatory factors. After 8 weeks of ocular hypertension, we observed a reduction in the number of excitatory and inhibitory synapses, dendritic spines, and activation of glial cells in the primary visual cortex contralateral to the affected eye. These findings suggest that glaucoma not only directly damages the retina but also induces alterations in synapses and dendritic spines in the primary visual cortex, providing new insights into the pathogenesis of glaucoma.